The Expression of Parenthood through the Oral Tradition of Storytelling - (:unkn) unknown (My University, 2016)
It is a time of great upheaval for Bwa young people due to the significant increase in formal schooling and the development of youth labour migration since the 1990s. In such a context, can the educational relationships depicted in traditional folktales be considered subversive, or are they indicative of a new situation where parents are struggling to fulfil their roles? More fundamentally, are parents the best people to educate their own children? This article approaches the educational parenting relationship by investigating the contrasting child figures identified in a corpus of 39 folktales. A first contrast is between the ill-treated orphan and the spoilt child. Likewise, the presence of an obedient child counterbalances the more frequently encountered naughty or difficult children. Lastly, different types of extreme child characters capture our attention, obliging us to think more deeply about their parents’ role in their education. The parent-child relationships in these folktales might seem paradoxical and even subversive, because in them we encounter children who are more mature and reasonable than their parents. However, this corresponds to a social reality, since nowadays children are learning outside of the family circle what they need to succeed in their adult lives.
Keywords: African Research